Comparison of antagonist mild and long agonist protocols in terms of follicular fluid total antioxidant capacity - Begum Aydogan Mathyk; Berna Aslan Cetin; Duygu Vardagli; Emel Zengin; Nigar Sofiyeva; Tulay Irez; Pelin Ocal (Elsevier, 2018)
Objective: A high dose of prolonged gonadotropins can yield higher numbers of oocytes and embryos. The high dose or prolonged regimens can be associated with ovarian hyperstimulation syndrome (OHSS), multiple gestations, emotional stress, economical burden and treatment dropout. In mild stimulation lower doses and shorter duration times of gonadotropin are used in contrast to the conventional long stimulation protocol in IVF. It has been proposed that supraphysiologic levels of hormones may adversely affect endometrium and oocyte/embryo. Also it has been proposed that oxidative stress (OS) may alter ovarian hormone dynamics and could be further affected by additional exogenous hormonal stimulation. Therefore our aim was to compare follicular fluid total antioxidant capacity (TAC) in antagonist mild and long agonist stimulations. Materials and Methods: Forty patients received antagonist mild stimulation, starting on the 5th day of their cycle and forty patients received long agonist treatment. Seventy-five patients undergoing their first IVF cycle were included in the final analysis. Follicular fluid (FF) samples were analyzed for estradiol (E2), antimullerian hormone (AMH) and TAC. Results: FF-Total antioxidant capacity (TAC) levels were higher in the long agonist group as opposed to the antagonist group [1.07 ± 0.04 mmol Trolox equivalent/L vs 1 ± 0.13 mmol Trolox equivalent/L] (Fig. 1). Pregnancy rates were not significantly different between the two treatments. The FF-TAC levels were not different among infertility etiologies (Fig. 3). FF-TAC levels did not have a direct correlation with pregnancy but a positive correlation with the total gonadotropin dose was observed. Conclusion: Patients with good ovarian reserves and under the age of 35 effectively responded to mild stimulation treatment. Using lower amounts of gonadotropin, yielded less FF-TAC levels in patients who underwent antagonist mild protocol. In patients under the age of 35, antagonist mild stimulation is a patient friendly and effective procedure when undergoing their first IVF cycle. Keywords: Anti müllerian hormone (AMH), Follicular fluid, In vitro fertilization (IVF), Mild stimulation, Total antioxidant capacity (TAC)